2015
DOI: 10.1097/sla.0000000000001045
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Laparoscopic and Open Nissen Fundoplication in Children

Abstract: Children operated with LF have a higher recurrence rate of GERD than those operated with OF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…In adult practice, laparoscopic fundoplication is considered the standard for proton pump inhibitor (PPI)‐resistant GORD, confirmed by a high‐quality RCT. Only a handful of RCTs focusing on ARS exist in the paediatric literature; these compared classical open versus laparoscopic fundoplication and wrap technique. Even these level 1 studies (according to the Oxford Centre for Evidence‐Based Medicine) did not report investigations for, and objective measures of, GORD both before and after operation.…”
Section: Discussionmentioning
confidence: 99%
“…In adult practice, laparoscopic fundoplication is considered the standard for proton pump inhibitor (PPI)‐resistant GORD, confirmed by a high‐quality RCT. Only a handful of RCTs focusing on ARS exist in the paediatric literature; these compared classical open versus laparoscopic fundoplication and wrap technique. Even these level 1 studies (according to the Oxford Centre for Evidence‐Based Medicine) did not report investigations for, and objective measures of, GORD both before and after operation.…”
Section: Discussionmentioning
confidence: 99%
“…21 The laparoscopic approach has been associated with a lower incidence of retching, shorter length of stay, and less morbidity, but a higher cost and longer operative times. 5, [22][23][24][25][26] Some authors have also reported a higher rate of recurrence of GERD in the laparoscopic approach compared with the open approach. 5, 23,27 In the past 5 years, there has been one prospective randomized trial comparing recurrence of GERD in children for the two approaches.…”
Section: Discussionmentioning
confidence: 99%
“…5, [22][23][24][25][26] Some authors have also reported a higher rate of recurrence of GERD in the laparoscopic approach compared with the open approach. 5, 23,27 In the past 5 years, there has been one prospective randomized trial comparing recurrence of GERD in children for the two approaches. 23 Eighty-seven children were randomized, and at a median follow-up of 4 years, more patients in the laparoscopic fundoplication (LF) group (37%) experienced recurrence of GERD compared with the open fundoplication (OF) group (7%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations